The dictionary of military terms (Skyhorse Publishing, 2015)
This is the comprehensive, standardized dictionary of military and associated terminology compiled and used by the Department of Defense. Divided into two sections, The Dictionary of Military Terms contains the terms and definitions approved for Department of Defense (DOD) and the North Atlantic Treaty Organization (NATO) use as well as a complete listing of commonly used abbreviations and acronyms. These military and associated terms, together with their definitions, constitute approved terminology for general use by all DOD components